Kung saan dumapo ang mga paruparo - Suarez, Gian Paulo
The film follows the story of Jared Buenviaje (not his real name), a 24-year-old closeted gay man, through his story of discovering his SOGIE and being in the closet. Through an anonymous online interview, Jared narrates the story of how his SOGIE developed from elementary to college, and how external factors like religion and homophobia forced him to repress his truth. He also shares his experiences being in the closet, his view on coming out, and his journey to self-acceptance. This film utilizes the theories of phenomenology, narratology, and queer theory combining dance, animation, and cinematic techniques to depict the story of a closeted person without forcing them to come out.